The Legal System and Violence: An Environmental Perspective - Foy Valencia, Pierre (2008)
This paper is about the relationship between the Law and violence from an environmental perspective. The author indicates that from a historic perspective there is complex relationship between the man and the nature. Then, the conception of the reality influence in how the legal system regulated some aspect related with the environment. From the dialectical interpretation, it is proposed the conflict between the human activity and nature. It is said that the nature reacts due to the affectation that suffers by the human being. Moreover, just the climate change does not affect the environment only, but many activities that are prejudicial also with the environment: the war activities, the modern biotechnologies activities, the bioterrorism threats. The author ask himself if it could talk about the violence against the nature. He indicates that it is reasonable to talk about it from a position like the democratic ecology, but not from an ecofundamentalism posture.  Now, he emphasizes in how the legal system should guarantee the environment. He says that is necessary reinforce the legal and extra legal protection of values such as water, the biological diversity to their preservation and defense given the threat of their existence.  In this line, the socio environmental conflicts emerge as an events associate to the environmental concern derivate from a possible affectation of the nature. Those conflicts have as causes the fear of the contamination, the social problem, the fundamental rights violation, the state institutional weakness, among other things. In turn, they have clear consequences in the political, social and economic aspects. Later, the author tell us about the relationship between the disaster and the environment. For it, it is said that should be an integration of different approaches to achieve an accurate answer. Likewise, he says that a culture of prevention should constitutes in a state policy to avoid damage and affectations to society. In this way, the technology and the sustainable development could be a source for the prevention and reduction of risks and disasters. Over the same topic, he says that Law must have a framework of action before the disasters occurrence. Finally, the relationship between the Law and the violence requires a broad perspective, as well as having in mind the vision of the new paradigms. Within them, the environmental dimension is a main aspect that it should not neglected.